Use of complementary medicines for osteoarthritis—a prospective study. Issue 5 (13th April 2004) - Zochling, J; March, L; Lapsley, H; Cross, M; Tribe, K; Brooks, P
Abstract : Background: Patients with osteoarthritis commonly use complementary and alternative medicines (CAM), either as an adjunct to or in place of conventional analgesics. Objectives: To undertake a prospective investigation of the prevalence of CAM use for osteoarthritis and the direct costs incurred. Methods: The subjects were 341 patients with osteoarthritis of the knee or hip drawn from central and northern Sydney, Australia, and comprising 83 community based patients and 258 awaiting joint replacement. Information on CAM use was obtained from prospective three monthly diaries. Variables of interest included health related quality of life scores. Prospective out of pocket costs were recorded over a 12 month follow up period. Results: The prevalence of CAM use was 40%, which falls within the range of previous studies. Average annual expenditure on CAM was A$32.25 (range 0 to 603.30). CAM users were more likely to be female (odds ratio (OR) 1.8 (95% confidence interval, 1.1 to 3.0)), reported a higher level of bodily pain (OR 0.97 (0.95 to 0.99)), and were less likely to purchase conventional analgesics (OR 3.3 (1.6 to 7.0)), either prescribed or over the counter. Vitamin supplementation was the most common CAM reported, followed by celery extract, fish oils, and garlic extracts. Conclusions: There are no good quality clinical trials to support the use of most preparations purchased by patients with osteoarthritis. There is a need for patient education on the risks and benefits of complementary medicine in osteoarthritis.